The Use of Quizizz Application to Increase the Students’ Motivation in Learning English - Ris Naufal Farid Rahman; Nurdin Noni; Muhammad Tahir (State University of Makassar, 2023)
This research is based on students’ motivation is still low, it is necessary to update in improving students' motivation and teachers' creativity in managing learning process. The purpose of this research was to identify whether the use of Quizziz application increases the students’ motivation in learning English at the 11th Grade of SMK YPKK Limbung and whether the use of Quizziz application as a medium for giving English exercises increases the students’ motivation in learning english at the 11th Grade of SMK YPKK Limbung. This research uses a quantitative approach method. The subjects of this research were all 24 students from XI.5 of SMK YPKK Limbung. the result showed that the mean of pre-test was 66,67% and the post-test was 80,42% and overall average score of students questinnaire obtained is 51.20. It means students’ motivation of the used Quizziz application are positive. Keyword: quizizz, students’ motivation, student’s achievement